(untitled) (Research, Society and Development, 2021)
Objective: Develop an e-book on home exercises for fatigue in climacteric women in digital format. Methodology: This is a cross-sectional, observational, prospective study with a quantitative approach. In which the validation process was composed of 7 experts in the thematic area of ​​the e-book using Pasquali’s theory. The Content Validity Index of greater than or equal to 0.78% was considered to ensure the validation of the material. The target audience was composed of 27 climacteric women, to choose the sample we followed the recommendation proposed by Fehring. In analyzing the data judged by the target audience, the items with a minimum agreement level of 75% in the positive responses were considered validated. Results: The items covered in the e-book validation instrument by the experts were divided into 2 blocks: structures and presentation, and relevance. Only 2 item had an agreement rate <0.78%, all other items were considered adequate with an agreement rate >0.78%. Overall, the responses from the target audience were in agreement regarding organization, writing style, appearance and motivation. With all items, it obtained an agreement rate greater than 75%. Conclusion: With this study, it was possible to conclude the importance of preparing an e-book based on the process of knowledge transmission and on the valuing of experiences between health professionals and the target audience.